Analisis penilaian postur kerja dengan Metode Ovako Work Posture Analysis System pada karyawan PT. ABC - Susiati, Devi; Kharismadani, Ayu; Cahyono, Manggi Dwi (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
PT. ABC is a company engaged in milling wheat into the largest flour in Indonesia. Every day the company has to produce as much as 6.500 tons/day of wheat flour to meet consumer needs. Therefore, employees must be able to work quickly and productively. The company has 11 Mill AB employees, not including millers. Many employees experience complaints and even injuries when carrying out activities on the production floor, starting from the screeningman, rollman, and shiftman. Given these problems, researchers used the Nordic Body Map Questionnaire in collecting primary data. Mill AB's employees have the most complaints about their backs because when working, employees often slouch. Furthermore, the data was processed using the OWAS method approach where the most complaints were in category 2, namely this attitude has the potential to cause damage to the musculoskeletal system. However, there is also a work attitude that is in category 3 where this attitude is also dangerous for musculoskeletal system disorders so work postures result in a very significant effect of tension.